Oral Complications in Hematopoietic Stem Cell Recipients: The Role of Inflammation - T. M. Haverman; J. E. Raber-Durlacher; W. M. H. Rademacher; S. Vokurka; J. B. Epstein; C. Huisman; M. D. Hazenberg; J. J. de Soet; J. de Lange; F. R. Rozema (Mediators of Inflammation)
Hematopoietic stem cell transplantation (HSCT) is widely used as a potentially curative treatment for patients with various hematological malignancies, bone marrow failure syndromes, and congenital immune deficiencies. The prevalence of oral complications in both autologous and allogeneic HSCT recipients remains high, despite advances in transplant medicine and in supportive care. Frequently encountered oral complications include mucositis, infections, oral dryness, taste changes, and graft versus host disease in allogeneic HSCT. Oral complications are associated with substantial morbidity and in some cases with increased mortality and may significantly affect quality of life, even many years after HSCT. Inflammatory processes are key in the pathobiology of most oral complications in HSCT recipients. This review article will discuss frequently encountered oral complications associated with HSCT focusing on the inflammatory pathways and inflammatory mediators involved in their pathogenesis.